2020
DOI: 10.1161/jaha.120.016612
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Cardiac Assessment for Diagnostic and Prognostic Stratification Following Myocardial Infarction

Abstract: Background Cardiovascular magnetic resonance imaging is considered the reference methodology for cardiac morphology and function but requires manual postprocessing. Whether novel artificial intelligence–based automated analyses deliver similar information for risk stratification is unknown. Therefore, this study aimed to investigate feasibility and prognostic implications of artificial intelligence–based, commercially available software analyses. Methods and Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
2
29
1
Order By: Relevance
“…Recently, automated analyses demonstrated feasibility and equally predictive prognostic value in 1017 patients following acute myocardial infarction compared to conventional analyses by trained and experienced medical personal 14 . Several previous studies applying the proposed automated algorithm showed consistently high interobserver reproducibility with experienced CMR observers 13 , 14 . The feasibility and reliability of automated LV analyses in clinical routine imaging is further underlined by the present data demonstrating high interstudy reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, automated analyses demonstrated feasibility and equally predictive prognostic value in 1017 patients following acute myocardial infarction compared to conventional analyses by trained and experienced medical personal 14 . Several previous studies applying the proposed automated algorithm showed consistently high interobserver reproducibility with experienced CMR observers 13 , 14 . The feasibility and reliability of automated LV analyses in clinical routine imaging is further underlined by the present data demonstrating high interstudy reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Future applications may expand to automated tissue characterisation e.g. scar quantification 14 as well as deformation imaging 24 . Deformation imaging has gained recognition for enhanced risk prediction beyond conventional volumetric derived functional analyses, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially patients having reduced cardiac performance and being classified to high-risk groups according to commonly used parameters can be assessed precisely and efficiently. Furthermore, since fully automatic strain and function quantification with dedicated post-processing software is feasible, these time-saving and highly reproducible methods might additionally facilitate the implementation of RM strain assessment in clinical routine [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…First software for automated post-processing of CMR images and subsequent deformation analyses have been introduced and utilized successfully [132,133]. As a result, post-processing times can be reduced, higher work efficiency might lead to significant cost reduction and results are less prone to observer variability [134]. Importantly, AI techniques are able to simultaneously evaluate deformation, cardiac volumes and ejection dynamics and may provide post-processing parallel to finishing the CMR protocol [135,136].…”
Section: Future Perspectives and Applications Of Cmr-based Deformation Analysesmentioning
confidence: 99%